IL‐6, IL‐8, MMP‐2, MMP‐9 are overexpressed in Fanconi anemia cells through a NF‐κB/TNF‐α dependent mechanism. Issue 12 (30th October 2014) - Epanchintsev, Alexey; Shyamsunder, Pavithra; Verma, Rama S.; Lyakhovich, Alex
<x xml:space="preserve">Abstract</x> Fanconi anemia (FA) is a rare autosomal recessive genetic disorder associated with a bone‐marrow failure, genome instability, hypersensitivity to DNA crosslinking agents and a predisposition to cancer. Mutations have been documented in 16 FA genes that participate in the FA‐BRCA DNA repair pathway, a fundamental pathway in the development of the disease and the presentation of its symptoms. FA cells have been characterized by an overproduction of cytokines, MAPKs, and Interleukins. Through this study we have identified the overexpression of additional secretory factors such as IL‐6, IL‐8, MMP‐2, and MMP‐9 in FA cells and in cells depleted of FANCA or FANCC and proved that their expression is under the control of NF‐κB/TNF‐α signaling pathways. We also demonstrated that these overexpressed secretory factors were effective in promoting the proliferation, migration, and invasion of surrounding tumor cells a fundamental event in the process of epithelial mesenchymal transition (EMT) and that they also modulated the expression of EMT markers such as E‐cadherin and SNAIL. Overall our data suggest that the upregulation of EMT promoting factors in FA may contribute to predisposing FA patients to cancer, thereby providing new insights into possible therapeutic interventions. © 2014 Wiley Periodicals, Inc.